2010
DOI: 10.1128/cvi.00258-10
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Rate of a “Fourth-Generation” HIV Antigen/Antibody Combination Assay in an Area of Low HIV Prevalence

Abstract: We retrospectively analyzed the performance of the Architect HIV antigen/antibody (Ag/Ab) combination assay in a tertiary health care center with a situation of low HIV prevalence. The specificity and positive predictive value (PPV) were 99.78% and 31.21%, respectively. However, the specificity and PPV could increase to 99.99% and 89.70% using an arbitrary cutoff value.Since the first HIV test was introduced in 1985, the performances of HIV screening assays have improved continuously. In particular, the HIV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 7 publications
7
38
0
Order By: Relevance
“…Similar results for the Architect procedure were recently reported by Muthukumar et al (14). Positive predictive values may be increased further by determining a different cutoff value appropriate for the population to be tested (15).…”
supporting
confidence: 82%
“…Similar results for the Architect procedure were recently reported by Muthukumar et al (14). Positive predictive values may be increased further by determining a different cutoff value appropriate for the population to be tested (15).…”
supporting
confidence: 82%
“…We also found true-positive samples with similar low values, which corresponded mostly to early stages of the infection, but also to group O HIV variants. These observations highlight the need for caution during the interpretation of indexes around the cutoff and the need for complementary analysis to avoid misinterpretation (18).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies with small samples have suggested a relationship between the S/CO ratio in HIV Ag/Ab assays and confirmed HIV infection or the HIV viral load (VL) (1,(6)(7)(8). As the somewhat time-consuming HIV WB test is the currently approved confirmatory test in Australia, we assessed the positive predictive value of the Abbott Combo assay in this low-prevalence population.…”
mentioning
confidence: 99%